Clima organizacional y desempeño laboral de los colaboradores de la empresa Transtur, Iquitos 2022 - Saavedra Manrique, Grey Marigen (2023)
The objective of this study is to know how the organizational climate and the job performance of the employees of the company Transtur, Iquitos 2022 are related. Because it will be carried out at a specific time during the specified period, this research is of the descriptive correlational type with a non experimental and cross-sectional design. We conclude that there is a significant correlation between the organizational climate and the work performance of the company's employees based on the calculated value of the Pearson correlation of the data collected regarding variables 1 and 2, which is equal to 0.942. Also, the two-sided sigma value is equal to 0.000 and is less than 0.05 by decision rule.